An exploratory PLS study of the academic success/failure - Basto, Mário; Abreu, Teresa; Vilhena, Estelha; Gonçalves, Joaquim; Carvalho, Mariana (Revista Contemporânea de Educação, 2020)
Strategies to combat academic failure in higher education rely on the identification and on the knowledge of the causes associated with it. To identify these causes, a questionnaire survey was implemented in a Higher School of Technologies and Engineering. Student-related aspects were those that exhibited the greatest impact on academic success/failure. Teachers and institution/curriculum exhibited an indirect impact through mediation by student-related aspects. Other variables were identified with a negative residual impact on academic success, such as: be displaced from the habitual residence, dislike to study and be a male. With a slightly more relevant impact, emerged the sleep time on the eve of the tests.